PENGEMBANGAN MEDIA MULTI MEDIA SEBAGAI BAHAN AJAR UNTUK MATA KULIAH ENGLISH COMMUNICATION FOR COMPUTER GRAPHICS (Sebuah Studi Kasus pada Program Studi Desain Komunikasi Visual Fakultas Ilmu Komputer Universitas Kuningan) - Roni Nursyamsu; Jerry Dounald Raharjaan; Yulyanto . . (NUANSA INFORMATIKA, 2021)
The Visual Communication Design Department is one of departments at Faculty of Computer Sciences, Kuningan University which offers English Communication for Computer Graphic courses to 6th semester students. This class requires the development of teaching materials that can help student understanding in studying these courses by collaborating with information technology assistance. Based on the results of observations in the previous semester, when the teaching, lecturer used classical lecture media in the form of power points, it did not provide understanding and interest in student learning.Based on the description above, to overcome the problem of lecturing in the English Communication for Computer Graphic course, the writers try to design multimedia teaching materials that include input material, content focus material, language focus material and tasks. The formulation of the problem in this research is: how to design and develop a multimedia learning media for the English Communication for Computer Graphic course that will be used in the teaching and learning process.The research on the developing multimedia learning in the English Communication for Computer Graphics course uses a Research and Development (RD) research framework. The writers develop software in the form of English learning media for the Visual Communication Design Department. The research process was carried out by developing a product and conducting a validity test. There are many kinds of software that supports use in the process of creating interactive multimedia applications with their own functions. In making interactive multimedia application, they used several software. The software used is as follows: Adobe Photoshop CS3, Adobe Flash CS3, and Adobe Audition 1.5. With this multimedia-based teaching material, it is hoped that students can be actively involved in English lecture activities, especially in the English Communication for Computer Graphic course, and they can easily understand the content of the material provided so that at the end of the lecture students can use spoken English as well as written in their life, especially in understanding and communicating English in certain fields English for Specific Purposes).Keywords: Learning Media, English Communication for Computer Graphic.